Combining one‐step Sanger sequencing with phasing probe hybridization for HLA class I typing yields rapid, G‐group resolution predicting 99% of unique full length protein sequences. (February 2017) - Tu, Bin; Masaberg, Carly; Hou, Lihua; Behm, Daniel; Brescia, Peter; Cha, Nuri; Kariyawasam, Kanthi; Lee, Jar How; Nong, Thoa; Sells, John; Tausch, Paul; Yang, Ruyan; et al.
Abstract : Background: Sanger‐based DNA sequencing of exons 2+3 of HLA class I alleles from a heterozygote frequently results in two or more alternative genotypes. This study was undertaken to reduce the time and effort required to produce a single high resolution HLA genotype. Materials and methods: Samples were typed in parallel by Sanger sequencing and oligonucleotide probe hybridization. This workflow, together with optimization of analysis software, was tested and refined during the typing of over 42, 000 volunteers for an unrelated hematopoietic progenitor cell donor registry. Next generation DNA sequencing (NGS) was applied to over 1000 of these samples to identify the alleles present within the G group designations. Results: Single genotypes at G level resolution were obtained for over 95% of the loci without additional assays. The vast majority of alleles identified (>99%) were the primary allele giving the G groups their name. Only 0.7% of the alleles identified encoded protein variants that were not detected by a focus on the antigen recognition domain (ARD)‐encoding exons. Conclusion: Our combined method routinely provides biologically relevant typing resolution at the level of the ARD. It can be applied to both single samples or to large volume typing supporting either bone marrow or solid organ transplantation using technologies currently available in many HLA laboratories.